Cultures of power : lordship, status, and process in twelfth-century Europe - Bisson, Thomas N. (Middle Ages series., 1995)
The authors of Cultures of Power proffer diverse perspectives on the prehistory of government in Northern France, Spain, Germany, the Low Countries, and England. Political, social, ecclesiastical, and cultural history are brought to bear on topics such as aristocracies, women, rituals, commemoration, and manifestations of power through literary, legal, and scriptural means.